Brassica vegetables as edible greens in Newfoundland - Spaner, D.; Lee, D. R. (Canadian Journal of Plant Science, 2001)
Turnip tops or greens, the early leaves of rutabaga (Brassica napus var. rapifera L.), are a traditional Newfoundland vegetable. Commercial farmers currently grow and market forage rape (B. napus L.) as greens. Our objectives were to determine why forage rape is now grown in preference to other Brassica crops and to examine potential greens alternatives. Seed from two cultivars each of three Brassicas [rutabaga, forage rape and forage kale (Brassica oleracea var. medullosa L.)] was used in: 1) a germination study at 5, 10, 15 and 20°C; 2) a growth study at constant temperature regimes of 12 and 18°C; 3) a 2 yr agronomic study; and 4) a sensory evaluation for appearance and taste as a boiled vegetable. Hobson rape, Dwarf Essex rape and the locally bred Brookfield rutabaga germinated, emerged and grew faster than both kale cultivars and Laurentian rutabaga at all controlled-temperature regimes. The two kale cultivars and Laurentian rutabaga did not exhibit adequate agronomic potential. Although the rape cultivars were among the top-yielding entries at most harvests, Brookfield rutabaga yielded greater leaf weight in both years of the agronomic study. Judges preferred the visual appearance of greens with dark green leaves, a characteristic of the forage rape cultivars studied, but favored the taste of boiled kale. Key words: Forage rape, kale, rutabaga, SPAD chlorophyll meter